Advances in Mn‐Based MOFs and Their Derivatives for High‐Performance Supercapacitor - Cheng, Honghong; Li, Jianping; Meng, Tao; Shu, Dong (Small (Weinheim an der Bergstrasse, Germany), 2024)
As the most widely used metal material in supercapacitors, manganese (Mn)‐based materials possess the merits of high theoretical capacitance, stable structure as well as environmental friendliness. However, due to poor conductivity and easy accumulation, the practical capacitance of Mn‐based materials is far lower than that of theoretical value. Therefore, accurate structural adjustment and controllable strategies are urgently needed to optimize the electrochemical properties of Mn‐based materials. Metal‐organic frameworks (MOFs) are porous materials with high specific surface area (SSA), tunable pore size, and controllable structure. These features make them attractive as precursors or scaffold for the synthesis of metal‐based materials and composites, which are important for electrochemical energy storage applications. Therefore, a timely and comprehensive review on the classification, design, preparation and application of Mn‐based MOFs and their derivatives for supercapacitors has been given in this paper. The recent advancement of Mn‐based MOFs and their derivatives applied in supercapacitor electrodes are particularly highlighted. Finally, the challenges faced by Mn‐MOFs and their derivatives for supercapacitors are summarized, and strategies to further improve their performance are proposed. The aspiration is that this review will serve as a beneficial compass, guiding the logical creation of Mn‐based MOFs and their derivatives in the future. This review gives a timely and comprehensive introduction on the classification, design, preparation and application of Mn‐based MOFs and their derivatives for supercapacitors. Specially, the recent advancement of Mn‐based MOFs and their derivatives applied in supercapacitor are highlighted. The challenges and outlooks of Mn‐MOFs and their derivatives for supercapacitors are also summarized.